Long-Term Genome Monitoring Retraces the Evolution of Novel Emerging Porcine Reproductive and Respiratory Syndrome Viruses - Xiang, Lirun; Xu, Hu; Li, Chao; Tang, Yan-Dong; An, Tong-Qing; Li, Zhen; Liu, Chunxiao; Song, Shuaijie; Zhao, Jing; Leng, Chaoliang; Qu, Xiangyang; Sun, Yingjun; et al. (Frontiers in Microbiology, 2022)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes tremendous economic losses to the swine industry worldwide. In China, novel PRRSVs have frequently emerged in recent years, but the evolutionary relationship among these viruses has remained unclear. In the present study, a four-year PRRSV genome-monitoring study was performed on samples from a pig farm. We observed that NADC30-like PRRSVs with higher mutation rates replaced HP-PRRSVs as the epidemic strains. We monitored the variation in the same PRRSV strain evolved in a pig herd over two years and observed that the low genomic similarity of NADC30-like PRRSVs results from rapid mutation. We also showed that recombination events between NADC30-like and QYYZ-like PRRSVs resulted in the complex recombination patterns of PRRSVs, which have formed gradually over time. Furthermore, recombination of the same strain can occur at different locations and increase the diversity of recombination events. Overall, these findings interpret the evolutionary patterns of novel and emerging PRRSVs, information that is crucial for PRRSV control.